Cross‐sectional study on the in‐herd prevalence of Mycoplasma hyopneumoniae at different stages of pig production. (15th January 2022) - Deffner, Pauline; Maurer, Roland; Cvjetković, Vojislav; Sipos, Wolfgang; Krejci, Roman; Ritzmann, Mathias; Eddicks, Matthias
Abstract: Background: A cross‐sectional study was carried out to assess the prevalence of Mycoplasma hyopneumoniae infections before vaccination in 3‐week‐old piglets and to gain information about infection dynamics. Methods: In 13 German and three Austrian farms with a known history of enzootic pneumonia, 790 piglets and 158 sows were sampled (blood samples, tracheobronchial swabs [TBS] [piglets], laryngeal swabs [LS] [sows]), and 525 pen‐based oral fluids (OFs) were collected in growing and fattening pigs. Laboratory diagnostics included enzyme‐linked immunosorbent assay (ELISA) and real‐time polymerase chain reaction (PCR) analyses. Results: Antibodies to M. hyopneumoniae were present in 87.5 per cent of all herds. Seroprevalence ranged from 0.0 to 100.0 per cent and 0.0 to 88.0 per cent in sows and piglets, respectively. M. hyopneumoniae ‐deoxyribonucleic acid (DNA) was present in 3.8 and 0.4 per cent of LS and TBS, respectively. Gilts had a 10.9 times higher chance being M. hyopneumoniae PCR‐positive than older sows. In 75.0 per cent of all farms, M. hyopneumoniae ‐DNA was present in OFs. Detection rate was significantly higher in OFs of 20‐week‐old than in younger pigs ( p < 0.001). Conclusion: Results indicate that M. hyopneumoniae infections of the lower respiratory tract in piglets are rare but highlight the role of gilts in maintaining infection in the herd. Collecting OFs seems promising for surveillance, if coughing occurs simultaneously.